TECHNOLOGIES FOR IMPROVING COMPOSITION AND DRAWING SKILLS BASED ON THE RULES OF COMPOSITION - Hasanboy Rakhimov Umarjon o’g’li; Odilbaeva Umida Zafarjon qizi (Galaxy International Interdisciplinary Research Journal, 2021)
The article deals with the rules and technologies of composition. The artist provides practical assistance in creating compositions, using visual skills and technologies.